Intertidal Foraging on Atolls: Prehistoric Forager Decision-Making at Ebon Atoll, Marshall Islands. (3rd April 2017) - Harris, Matthew; Weisler, Marshall
ABSTRACT: Prehistoric molluscan assemblages provide insights into long-term patterns of human landscape use, environmental change, and human impacts to marine resources. The investigation of forager decision-making regarding the selection of certain mollusc taxa and/or the exploitation of particular habitats is fundamental to understanding human-environment interactions in the past, and is relevant for understanding trajectories of human impacts to the intertidal zone in coastal settings. We document variability in the collection of molluscs at two archaeological sites on Ebon Atoll, Republic of the Marshall Islands: one on a windward, intermittently occupied islet, and the other on a permanently inhabited leeward islet. All molluscan taxa were assigned to a range of habitats within a hierarchical classification scheme for intertidal marine environments. The relative abundance of taxa from each habitat was used as a proxy for forager decision-making. We report a generalized, non-selective, foraging strategy focused on gastropod taxa from the high intertidal and supratidal. These results indicate that rather than focusing intensively on select taxa, intertidal foragers targeted particular marine habitats, taking advantage of the predictable behaviors of the molluscs that inhabit them.